Normal endometrial stromal cells regulate 17β-estradiol-induced epithelial-mesenchymal transition via slug and E-cadherin in endometrial adenocarcinoma cells in vitro. (2nd January 2017) - Zhang, Hui; Li, Hongyan; Qi, Shasha; Liu, Zhao; Fu, Yibing; Li, Mingjiang; Zhao, Xingbo
Abstract: Stroma–tumor communication participates in the pathogenesis of endometrial carcinomas. In previous studies, we found that normal stromal cells inhibited the growth of endometrial carcinoma cells. Here, we investigated the role of normal stromal cells in the epithelial-mesenchymal transition (EMT) of endometrial carcinoma cells and explored the possible mechanism implied. We found that conditioned medium (CM) by normal endometrial stromal cells (NSC) reduced cell growth and induced cell apoptosis in Ishikawa cells. CM by NSC inhibited 17β-estradiol-induced cell growth and apoptosis decrease in Ishikawa cells. Moreover, CM by NSC inhibited the migration and invasion, and 17β-estradiol-induced migration and invasion in Ishikawa cells. Meanwhile, CM by NSC decreased Slug expression and 17β-estradiol-induced Slug expression, increased E-cadherin expression and abolished 17β-estradiol-induced E-cadherin reduction in Ishikawa cells. In conclusion, normal stromal factors can inhibit 17β-estradiol-induced cell proliferation and apoptosis inhibition, and abolished 17β-estradiol-induced EMT in endometrial cancer cell via regulating E-cadherin and Slug expression.